Research on the Enterprise Knowledge Management in Dynamic and Complex Environment - Zhongwei Zhao; Bingsheng Zhao (2009 International Conference on Management and Service Science, 2009)
This paper first carried on the analysis to the relations between the environment and enterprise knowledge management, and then carried another analysis to the dynamic and complex trend in environment development. According to the dynamic and complex environment, we build a knowledge management model for sustainable competitive advantage. Based on this, we put forward some suggestions from knowledge integration and knowledge application for enterprise knowledge management in dynamic and complex environment.